The Mathematical Creative Thinking Ability in Solving HOTS Problems Based on Cognitive Style and Gender - Rofi Nur'aulia Syifa; Hella Jusra (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2022)
Creative thinking may determine individuals' problem-solving ability, including mathematics. This study aimed to analyze and describe the creative mathematical thinking ability to solve Higher Order Thinking Skills (HOTS) problems by considering students' cognitive styles and gender roles. This descriptive qualitative study employed a purposive sampling method to select the study sample with criteria: senior high school students, males, and females, with reflective and impulsive cognitive styles. The study participants were four students, comprising one pair of male and female students of reflective and impulsive cognitive styles. Data were obtained by conducting the Matching Familiar Figures Test (MFFT), mathematical creative thinking abilities test to solve HOTS problems, and interviews. Data were analyzed with data reduction, data display, and conclusion. Method triangulation was then performed to test the validity of this study by comparing the datasets. Results of this study revealed that all male students with a reflective and impulsive cognitive style could demonstrate fluency indicators of mathematical creative thinking ability. While, only half of the female counterparts were able to do so. Furthermore, this study's results indicated that both male and female students could not solve HOTS problems in flexibility and novelty indicators of mathematical creative thinking ability. Keywords: cognitive styles, gender, HOTS, creative thinking.